Recurso educativo y aprendizaje del control prenatal dirigido a estudiantes de la carrera de Medicina de la Universidad Nacional de Loja - Tene Hurtado, María Belén (2024)
The learning and acquisition of skills through scenarios based on real-life situations are fundamental tools in medical education, as they promote more efficient consolidation of knowledge and enhance the learning experience for healthcare professionals. The main objective of this research was the creation of educational resources based on simulation for learning prenatal care, aimed at medical students. The specific objectives were: to develop a practical guide for learning prenatal care, create an educational video resource, and assess the knowledge acquired through the Objective Structured Clinical Examination (OSCE) applied to the students. A mixed design of prospective cross-sectional cohort was used for the study, with 38 students from the 10th cycle of the Human Medicine program during the October 2022- March 2023 semester. These students participated in a workshop using the created educational resources, followed by an assessment through the OSCE. The results showed that 71.05% of the participants (27 students) achieved an outstanding grade after completing 17 activities in the OSCE. Meanwhile, 28.95% (11 students) obtained a very good grade, completing between 15 and 16 activities correctly. These results indicate that the educational resources used significantly contributed to the development of skills for learning prenatal care. In conclusion, the implementation of these educational resources represents a valuable and accessible tool for consolidating knowledge